Effectiveness of Antibacterial Extract Bawang Suna (Allium schoenoprasum L.) against Methillicin-Resistant Staphylococcus aureus (MRSA) using Total Plate Count - Kania Claranisza Agustin; Fatmaria Fatmaria; Indria Augustina (Majalah Obat Tradisional, 2022)
Methicillin-Resistant Staphylococcus aureus (MRSA) infection can cause death which has caused the World Health Organization (WHO) in 2017 to issue a list of priority pathogens (one of which is MRSA) for the search for new antibiotic research. Bawang suna (Allium schoenoprasum L.) is believed to be able to inhibit the growth of the number of MRSA bacterial colonies because it contains saponins, alkaloids, flavonoids, tannins, triterpenoids, and steroids. The research was aimed to prove extract of bawang suna(Allium schoenoprasum L.) has effectiveness as an antibacterial to inhibit the growth of MRSA. True experimental design research design with cup count method using posttest only control design to compare the results of observing the number of MRSA bacterial colonies with and without treatment (control group) with serial dilution sampling technique serial dilution using a ratio of 1:5. The treatment used 1 ml an extract of bawang suna (Allium schoenoprasum L.) in the control group. 1 ml an extract of bawang suna (Allium schoenoprasum L.) gave a significant and closely related effect to inhibiting the growth of MRSA bacteria at a dilution level of 10-3 of 3288,50 + 1117,98, a dilution level of 10-4 of 379,25 + 33,75, and a 10-5 dilution rate of 42,00 + 8,68. The decrease in the number of MRSA bacterial colonies was due to the extract of bawang suna (Allium schoenoprasum L.) containing compounds: saponins, alkaloids, flavonoids, tannins, triterpenoids, and steroids that could prevent the growth of MRSA bacterial colonies. The extract of bawang suna (Allium schoenoprasum L.) as much as 1 ml using Total Plate Count (TPC) with serial dilution testing technique has a significant effect on dilutions of 10-3, 10-4, and 10-5 as an antibacterial to inhibit the growth of MRSA bacteria